2013
DOI: 10.5607/en.2013.22.4.301
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-Binding Heptamer Confers Anti-Inflammatory Effects in Primary Microglia Culture

Abstract: High mobility group box 1 (HMGB1) is an endogenous danger signal molecule. In the postischemic brain, HMGB1 is massively released during NMDA-induced acute damage and triggers inflammatory processes. In a previous study, we demonstrated that intranasally delivered HMGB1 binding heptamer peptide (HBHP; HMSKPVQ) affords robust neuroprotective effects in the ischemic brain after middle cerebral artery occlusion (MCAO, 60 minutes). In the present study, we investigated HBHP-induced anti-inflammatory effects on mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Finally, Hmgb1 interacts with and represses Mecp2 69 . However, LPS + IFNγ downregulates Hmgb1 , thus increasing Mecp2 expression and blocking secretion of pro-inflammatory mediators 70 , 71 . Thus, these results suggest that LPS + IFNγ treatment reduces genes involved in neuropathic pain, as well as microglial migration and proliferation, whereas it also promotes some anti-inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Hmgb1 interacts with and represses Mecp2 69 . However, LPS + IFNγ downregulates Hmgb1 , thus increasing Mecp2 expression and blocking secretion of pro-inflammatory mediators 70 , 71 . Thus, these results suggest that LPS + IFNγ treatment reduces genes involved in neuropathic pain, as well as microglial migration and proliferation, whereas it also promotes some anti-inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Weber and colleagues (2015) reported that acute exposure to inescapable tail shock increases microglial HMGB1 release and sensitization to ex vivo LPS challenge 1 day after stress [19]. Pharmacological blockade of HMGB1 signaling using the selective antagonist BoxA, attenuated HMGB1-mediated potentiation of LPS responses in cultured primary microglia (22, 23). In addition, in vivo administration of glycyrrhizic acid (GZA), a non-selective antagonist of HMGB1, protects rodents against LPS-induced depressive-like behaviors (24) and cognitive deficits following fluid percussion injury (25).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several approaches to block HMGB1-mediated inflammation and thereby protecting neurovascular unit, including neutralizing monoclonal antibody (mAb) [ 13 , 14 ], N-terminal domain of HMGB1 (competitively binds to receptors) [ 31 ], non-specific inhibitors like glycyrrhizin [ 32 ], and blocking peptide (HBHP) [ 15 , 19 , 33 ]. Among them, mAb requires intracerebroventricular injection, whereas HMGB1 N-terminal domain and glycyrrhizin lack target specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Different doses of TAT-HBHP (YGRKKRRQRRR-HMSKPVQ, 1, 5, 10 mg/kg) were intravenously administered after tPA treatment within 30 min (Fig. 3a ) [ 15 , 19 ]. TAT-scramble peptide (YGRKKRRQRRR-PMQSKHV, 5 mg/kg) was employed as vehicle control.…”
Section: Methodsmentioning
confidence: 99%